2016
DOI: 10.1080/15374416.2016.1141358
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Relations Among Parental Monitoring Strategies, Knowledge, and Adolescent Delinquency in a Racially Diverse At-Risk Sample

Abstract: Parents raising youth in high-risk communities at times rely on active, involved monitoring strategies in order to increase both knowledge about youth activities and the likelihood that adolescents will abstain from problem behavior. Key monitoring literature suggests that some of these active monitoring strategies predict increases in adolescent problem behavior rather than protect against it. However, this literature has studied racially homogenous, low-risk samples, raising questions about generalizability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 78 publications
4
22
0
7
Order By: Relevance
“…Nonetheless, this is nothing more than a theoretical hypothesis that should be tested in future empirical studies. Additionally, although we do not know whether there is a direct relationship between the two variables, this work confirms that there exists a relationship between reduced parental monitoring and increased juvenile delinquency, as is well known in criminology (Bendezú et al 2016;Stattin and Kerr 2000).…”
Section: Discussionsupporting
confidence: 70%
“…Nonetheless, this is nothing more than a theoretical hypothesis that should be tested in future empirical studies. Additionally, although we do not know whether there is a direct relationship between the two variables, this work confirms that there exists a relationship between reduced parental monitoring and increased juvenile delinquency, as is well known in criminology (Bendezú et al 2016;Stattin and Kerr 2000).…”
Section: Discussionsupporting
confidence: 70%
“…Our findings therefore suggest that in more at-risk settings, parents may engage in more active parental monitoring strategies consistently over time in order to ensure the safety and well-being of their children (Burton & Jarrett, 2000; Gartstein et al, 2014; Supplee et al, 2007). This interpretation is further supported by findings from analyses with the same sample as was included in the current study (Bendezú et al, 2018), which highlighted the important role of parental discussions in more at-risk contexts. Furthermore, and counter to our hypotheses, we also observed no change in child communication with parents over time.…”
Section: Discussionsupporting
confidence: 84%
“…Various contextual factors that place these families at-risk (e.g., significant environmental risks, parental employment that keeps them away from the home for many hours/overnight) may mean that parents cannot wait for their children to disclose their activities and whereabouts. A recent study with a racially diverse sample of families living in at-risk neighborhoods (the same sample as described in the current study) indicated that parental discussions of daily activities (an aspect of parental solicitation) was the strongest predictor of parental knowledge as measured in adolescence (i.e., Grades 9 and 10; Bendezú et al, 2018).…”
mentioning
confidence: 60%
See 2 more Smart Citations